An exploration of experts' views on the integration of vertical greenery as public art in Malaysian cities - Abu Bakar, Nur Izzah; Mansor, Mazlina; Harun, Nor Zalina (University Putra Malaysia, 2015)
Vertical greenery (VG) is plants that can be grown on, up, or against internal or external walls of buildings or as freestanding structures. An urban area is in need of more greenery in its surroundings and one method is by increasing the implementation of VG in urban areas. This is due to various benefits gained by implementing VG in terms of the aesthetic, economic and environment aspect. Furthermore, to sustain its usage, VG must be explored creatively. Public art (PA) is a structure or a form that contains an artistic expression that is located in a freely accessible city’s public space. Sadly, PA in Malaysia is often used merely to decorate and fill-up the public spaces. This scenario is actually contradicting with the ultimate objective of PA, which is it should serve as an artistic expression that can be used, appreciated and has benefits to the public. Hence, there is a need to improve the selection and appearance of PA in Malaysian cities. With this premise, this research sets out to explore the potentials of VG to be integrated as a PA in the city’s public space. This research is a part of author’s Master Degree thesis titled “Analyzing the Potentials of Vertical Greenery in Malaysian Urban Context”. The aim of this paper is to discover the perspectives of experts in landscape architecture and PA field on the potentials of the integration. This is because, a majority of research in VG, especially in Malaysia focuses on environmental and technical aspects of VG, rather than looking at creative methods to approach VG. This paper presents two research objectives; (i) to identify the potentials of its integration from experts in the field of landscape architecture and PA and, (ii) to study the attributes of VG as a PA from their perspectives. Semistructured interviews were conducted with two experts in VG and two experts in PA. Findings suggest that there are five potentials for VG as a PA: to use the abundant Malaysian natural resources, to be a leader in VG for South East Asia (SEA) region, to support the nation’s green aspiration, sustainability perspectives and to have an artistic green wall. Meanwhile, there are 17 attributes of VG as PA listed by the experts; (a) large size and scale, (b) fair percentage of greenery, (c) proper maintenance, (d) uncommon geometric patterns, (e) using unconventional materials, (f) creative implementation method, (g) direct art intervention, (h) surprise elements, (i), out of the norm design, (j) wonder about the creative works, (k) the VG needs to have some meaning behind it, (l) combine material of living and non-living things, (m) creative utilisation of plants, (n) use recycled material, (o) continuing with the surroundings, (p) interaction with public, (q) visibly seen by the public and (r) impactful. Thus, the findings imply that all experts were in agreement and believe that VG has high potential to be integrated as a PA. Finally, the findings also reveal several measures to improve the selection and appearance of PA as VG in the Malaysian cities.